Problem dan Model Pembelajaran Membaca Al-Quran Anak Usia Dini Masa Pandemi di Kabupaten Jember - Fajar Abdillah; Yeni Rofiah; Nur Azizah (LPPM IAIN Sorong, 2021)
This research discusses what is the problem of learning to read the Koran for early childhood during the pandemic and how the learning model to read the Koran for early childhood. Researchers used qualitative research methods. This type of research is a case study with a multi-site type. The results showed that the problem of learning to read the Koran for early childhood during the pandemic consisted of external problems which included limited facilities and infrastructure and difficult internet access; and internal problems which included the characteristics of students who were still at an early age, and students' low learning motivation while in home. Meanwhile, the learning model to read the Koran for early childhood during the pandemic consists of a traditional model carried out in shifts at school or at the nearest teacher's house with the application of health protocols and a blanded (mixed) model between online and offline, in terms of providing material and assignments carried out online. while the evaluation is done offline.